Paul Tillich and Religious Socialism: Towards a Kingdom of Peace and JusticehKirk R. MacGregor - MacGregor, Kirk R. (Lexington Books, 2021)
This constructive theological work enhances Tillich's German religious socialism by creatively integrating it with Tillich's theological insights throughout his American career. Bringing Tillich into conversation with contemporary developments in just peacemaking, this book presents a refurbished version of religious socialism.